Comparison of quality of chest compression in different postures using female patient manikin - Kaoru Kobayashi; Yuri Ishida; Shota Ichikawa; Hiroto Ito; Asahi Kobayashi; Yukinobu Hiiragi (Japanese Society of Physical Fitness and Sports Medicine, 2024)
Early cardiopulmonary resuscitation (CPR) intervention is critical for saving individuals experiencing sudden cardiac arrest. Manikins are considered useful for CPR training, but their level of realism is low, given the visible structural differences in the chests of biological men and women. However, to our knowledge, no study has examined whether a patient's sex has an impact on the performance of chest compression. Therefore, this study aimed to investigate the quality of chest compression in female patients, in relation to the rescuers' posture. This single-center cross-sectional study was conducted from July to October 2023 on 34 healthcare professional university students. Two postures for chest compression were analyzed: 1) kneeling beside the patient's chest (conventional compression) and 2) straddling the patient (straddle compression). The mean age of the 34 participants (18 men and 16 women) was 21.2 ± 0.6 years. Significant differences were found in mean compression depth (p = 0.005) and appropriate compression ratio (p = 0.013) between the conventional and straddle compression, but not in other parameters. In conclusion, the rescuers' posture during chest compression in female patients affects the compression depth and depth ratio. Straddle compression may facilitate the provision of well-balanced compressions of appropriate depth and depth ratio. These findings can be applied to CPR training and provide guidance for administering chest compression to female patients.